2006
DOI: 10.1007/s11010-006-9166-y
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of connexin 43 in the diabetic rat heart

Abstract: In the Streptozotocin-induced diabetic rat heart, a decrease in the conductivity and suppression of electrical cell-to-cell coupling were observed. To clarify this mechanism, the present study was performed to investigate alterations of the gap junction connexin 43 (Cx43) using immunoblotting, immunohistochemistry, electron-microscopic analyses. An enhanced activation of PKCepsilon, an augmentation of PKCepsilon-mediated phosphorylation of Cx43, a decrease in the total amount of Cx43, a reduction in the area o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
68
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 39 publications
6
68
1
Order By: Relevance
“…The present study did not observe the increase in Cx43 amount after treatment with these inhibitors, which were proved in other studies. 39,40) We suppose the discrepancy with our results possibly due to differences in cell type or cell culture conditions, or a short treatment time, for that some reports demonstrated that treatment with Leu or ALLN for 5 h was not sufficient to increase intracellular Cx43 amount. 43,44) The mechanisms underlying the increase in Cx43 degradation induced by 2-APB and DPBA are unknown.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…The present study did not observe the increase in Cx43 amount after treatment with these inhibitors, which were proved in other studies. 39,40) We suppose the discrepancy with our results possibly due to differences in cell type or cell culture conditions, or a short treatment time, for that some reports demonstrated that treatment with Leu or ALLN for 5 h was not sufficient to increase intracellular Cx43 amount. 43,44) The mechanisms underlying the increase in Cx43 degradation induced by 2-APB and DPBA are unknown.…”
Section: Discussioncontrasting
confidence: 82%
“…37,38) To delineate the degradation site of Cx43 induced by 2-APB and DPBA, cells were treated with the two agents and specific inhibitors of the lysosomal and proteasomal pathways for 4 h. Leupeptin (Leu), a potent lysosomal inhibitor, is widely used in the study of Cx43 degradation. 39,40) Proteasomal proteolysis is inhibited by ALLN, which is highly specific for the proteasomal pathway. 41) As shown in Fig.…”
Section: Effects Of Lysosomal and Proteasomal Inhibitors On The 2-apbmentioning
confidence: 99%
“…Connexin43 is a type of gap junction protein, which is found in the intercalated disk of the myocardium. It is associated with the transfer of impulses between adjacent cardiac muscles (Lin et al, 2006;Kostin, 2007). In our study, we found a decrease in expression of connexin43 in the Dahl S group when compared with the Dahl R group, which indicated that impulse transfer was impeded.…”
Section: Cardiac Lymphedema and Myocardial Fibrosissupporting
confidence: 43%
“…Enhanced phosphorylation of Cx43 may be in part attributed to increased expression of PKCε. Our previous studies suggest that enhanced Cx43 phosphorylation due to activation of PKCε was linked with slowing of myocardial conduction and decreasing susceptibility of diabetic or hypothyroid rat hearts to malignant arrhythmias (Lin et al 2006(Lin et al , 2008Bacova et al 2013). In contrast, reduced expression of PKCε accompanied by decreased Cx43 phosphorylation in hyperthyroid rat hearts was highly proarrhythmic .…”
Section: Discussionmentioning
confidence: 97%